Plan estratégico de desarrollo institucional y comercial para el fortalecimiento de la microempresa "Seda y Cacao Artesanal Cía. Ltda." - González, Andrea B. (2019)
This research project took place at the Seda y Cacao Artesanal Cía. Ltda. microenterprise, whose fundamental purpose consisted in the design of a Strategic Plan for Commercial Development for this company, located in Ibarra, Imbabura province, whose business name is based on the production and marketing of products derived from cocoa fruit. In order to fulfill this objective, an exhaustive analysis of the literature related to the research topic was carried out, thus knowing the different theoretical perspectives that strengthen the development of the study. In this way, an analysis of the current situation of the investigated organization was established, determining as main flaws that it does not adequately develop a management based on strategic planning, evidencing a lack of advertising actions, insufficient goods production, shortcomings in the mission and vision declaration, among other factors. That´s the reason the Institutional Strategic Plan was developed, which contains the design of the corporate image of Seda y Cacao Artesanal Cía. Ltda. microenterprise, its strategic projection, strategic objectives related to the key results areas and strategies linked to action plans. Finally, a budget for the implementation of the Strategic Plan adjusted to the characteristics and possibilities of the company under study was presented.